Exploring drivers and management strategies of informal patient payments in hospitals: A qualitative study in Iran - Ali Reza Yusefi; Jamshid Bahmaei (PLoS ONE, 2026)
Background Informal patient payments remain a persistent and multifaceted challenge in many health systems, particularly in low- and middle-income countries. These payments, often made outside official channels, can undermine equity, transparency, and trust in healthcare delivery. This qualitative study aimed to explore the underlying causes of informal payments and identify feasible management strategies from the perspectives of key stakeholders. Methods This applied study was conducted using a qualitative method and semi-structured interviews between September 10, 2024, and January 17, 2025. A total of 31 participants, including senior policymakers from the Ministry of Health, hospital managers, medical specialists, nursing managers, hospital supervisors, health economics and healthcare management faculty members, and patients with experience of informal payments in Iranian hospitals, were selected through purposive and snowball sampling methods. Latent content analysis was employed for data analysis, and MAXQDA software (version 2022) was used to extract the main and subcategories. Results Six main themes and 39 subcategories were identified regarding the causes of informal patient payments. From the perspectives of policymakers, physicians, and service providers, four main themes with 27 subcategories emerged, including factors related to salaries and benefits, structural and organizational issues, laws and regulations, and ethical and cultural considerations. From the perspective of service recipients, two main themes with 12 subcategories were identified, covering service-related and cultural factors. Regarding management strategies to address informal payments, three main themes with 14 subcategories were found, encompassing structural, legal, and cultural approaches. Conclusion Informal payments in hospitals are driven by a complex interplay of economic, structural, legal, cultural, and ethical factors. Addressing this issue requires a multifaceted strategy, including tariff reform, strengthening legal and regulatory frameworks, promotion of professional ethics, improved service delivery systems, and public awareness campaigns. Sustainable reduction of informal payments demands coordinated efforts across all levels of the health system.